Austral Hepaticae 50. Gackstroemia in New Zealand, together with an interesting new species - Engel, John J. (Phytotaxa, 2013)
Gackstroemia novae-zelandiae sp. nov. is added to the genus Gackstroemia, a genus confined to the south temperate. The new species has been previously included within G. weindorferi, and is endemic to New Zealand. Gackstroemia weindorferi of New Zealand and Australia (Tasmania, Victoria, and New South Wales) and G. alpina are also treated.